PELATIHAN DAN PENDAMPINGAN PENULISAN ARTIKEL ILMIAH BAGI GURU-GURU MTs ISLAMIYAH MEDAN - Dila Handayani; Fitry Wahyuni (LPPM STKIP AL MAKSUM, 2022)
This Community Service activity was carried out to provide training and assistance to teachers at MTs Islamiyah Medan where teachers at MTs Islamiyah Medan still faced difficulties in understanding the preparation of scientific articles. Many teachers do not want to publish their research results because they do not understand how to compile scientific articles. This is the background that teachers at MTs Islamiyah Medan are not interested in writing scientific articles. The main purpose of Community Service this time is to provide training and assistance on how to write journal articles that you want to publish, provide motivation, encouragement, and support for teachers to write, and assist teachers in writing scientific articles. This training activity was carried out at MTs Islamiyah Medan with 15 teachers as participants. Training and mentoring are held offline, so teachers have direct opportunities to ask questions and practice interactively. The training methods and instruments used in this activity are as follows: (1) Lecture method. When using this method, the Community Service Team gives lectures using PPt and examples of Sinta 2-6 (2) accredited journal articles, discussion and question and answer methods. The instrument used was in-depth interviews with participants. Participants can ask questions about writing scientific articles and they will be answered by the Community Service Team. Participants also asked about examples of articles distributed to participants. (3) Simulation method. Participants begin to practice using the articles that have been sent. The instrument used is an in-depth interview. The training and mentoring held by the PKM Team is expected to provide useful knowledge for teachers in compiling scientific articles to be published related to teaching and learning.